KONSELING ALKITABIAH LUKA BATIN DAN RELEVANSINYA DENGAN MINAT BELAJAR ANAK-ANAK SEKOLAH MENENGAH TEOLOGI KRISTEN (SMTK) WAIKABUBAK SUMBA BARAT - Tonny Andrian Stefanus (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2021)
By carrying out the activities of the lecturers through community service, in carrying out Biblical counseling teaching and training, it will improve the teacher's ability to develop counseling for children who are hurt mentally This is proven when a teacher provides a biblical understanding of counseling, it will certainly affect learning and increase the motivation for children's interest in learning. The writing method for reporting the implementation of biblical counseling for the inner wounds of the children of the Waikabubak West Sumba Christian Theology Middle School (SMTK) with an interest in learning children is through training, teaching and seminars. This activity took place in stages in 2014, 2015 and 2017. The results achieved from this implementation activity were the increasing quality of the Spirituality, Mentality and Intellectuality of the Sumba Church Community, especially the Waikabubak Christian Theological High School, West Sumba.